Belaúnde Terry: : una imagen más allá de la narrativa - Llanos Illescas, Luis Fernando (2024)
Fernando Belaúnde Terry, who was twice president of the republic in 1963-1968 and  1980-1985, is considered by Peruvian historiography as a statesman and example to follow. However, the purpose of this article is to move away from the legend of a president who sought the country's industrialization and focuses on the figure of the man with all his successes and errors. Among the latter are: the massacre of the indigenous community in Matses in 1964; the burning of books in 1967 and the violent handling by the State during the beginning of the Internal Armed Conflict. These errors as some call them are truly crimes and must be recorded. For this reason, to know the two versions of the character, we will begin by making a short biography of the former president and then address his crimes. We will end by contrasting this profile with the idea we have of Belaúnde Terry in the vast biography that his loved ones have written.